Novel approach for direct methods in medical imaging using compressive sensing - Freitas, Gabriel Luis de Araújo e (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.